A lignolytic fungi with laccase activity isolated from Malaysian local environment for phytochemical transformation purposes - Alfarra, Helmi Yousif; Hasali, Nor Hazwani; Omar, Muhammad Nor (International Science Congress Association, 2013)
The main aim of the current study is to isolate a fungi with laccase activities to be used for transformation of phytochemicals isolated from the same environment as an approach to produce novel pharmaceutical products. In our study, laccase producing fungi was isolated from samples taken from a tropical trees barks which grown in the International Islamic University Malaysia, Kuantan campus using different chromogenic substrates on the agar plates such as ABTS, Tannic Acid, Azure B and Guaiacol. It was found the isolated fungi has excellent ability to produce laccase. The conclusion of this study confirm here that using ABTS is very useful to isolate laccase producing fungus. The microscopic visualization showed the characteristics of white-rot fungi. Further molecular identification still ongoing to check the complete identity of our fungi.